Desain modul interaktif menggunakan aplikasi course lab berbasis pendekatan saintifik pada materi usaha, energi, dan momentum - Arike Ikhfa Safitri; Festiyed Festiyed; amali putra (PILLAR OF PHYSICS EDUCATION, 2019)
The research objective is to produce an interactive module using a valid course application based on a scientific approach. This is based on the reality of the field in SMAN 1 Batusangkar, seen that in learning more students accept and copy what is delivered by the teacher due to the method used in learning that is the lecture method that focuses on teacher learning (teacher centered). During the learning process not yet seen all the components of the scientific approach implemented by students due to lack of teaching materials or modules. This research is a mixed-method research which is a combination of qualitative and quantitative approaches. This study aims to determine the validity of an interactive module product in accordance with the steps of making teaching materials in the form of modules according to the Ministry of National Education (2008) such as: 1) main display / cover, 2) display of learning instructions, 3) display of competencies to be achieved, 4 ) content of the material, 5) supporting information, 6) Exercises, 7) Student worksheets, and 8) Evaluation. Based on the research that has been done, two research results are obtained. First, this research produces a product in the form of an interactive module using the Course Lab application based on a scientific approach to business material, energy, and momentum. And the results of the second study were the results of the validity test conducted by three UNP Physics lecturers and one physics teacher at SMA 1 Batusangkar with 89.4 validity results with very valid validity criteria. So it can be concluded that the interactive module using the Course Lab application based on a scientific approach to the material business, energy, and momentum is very valid and can be used to test the practicality and effectiveness by subsequent researchers.